2022
DOI: 10.1096/fj.202101713rrr
|View full text |Cite
|
Sign up to set email alerts
|

OCT4/POU5F1 is indispensable for the lineage differentiation of the inner cell mass in bovine embryos

Abstract: The mammalian blastocyst undergoes two lineage segregations, that is, formation of the trophectoderm and subsequently differentiation of the hypoblast (HB) from the inner cell mass, leaving the epiblast (EPI) as the remaining pluripotent lineage. To clarify the expression patterns of markers specific for these lineages in bovine embryos, we analyzed day 7, 9, and 12 blastocysts completely produced in vivo by staining for OCT4, NANOG, SOX2 (EPI), and GATA6, SOX17 (HB) and identified genes specific for these dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…During mammalian preimplantation development, OCT4/POU5F1 plays a critical role as a transcription factor, with diverse functions [53], encompassing the maintenance of pluripotency and the regulation of differentiation events [54]. Our results showed that the pluripotency factor OCT4/POU5F1 is consistently expressed across the entire bovine Day 7 blastocysts, similar to the observations by Simmet et al [55,56] and Kirchhof et al [57] in both in vivo and in vitro produced bovine embryos on days 7, 9, and 12. Furthermore, we observed an increased expression of POU5F1 and NANOG transcripts in blastocysts produced with miR-148b supplemented throughout the entire period of IVC or during days 1 to 4 of IVC to simulate the miRNA effect in the oviduct.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…During mammalian preimplantation development, OCT4/POU5F1 plays a critical role as a transcription factor, with diverse functions [53], encompassing the maintenance of pluripotency and the regulation of differentiation events [54]. Our results showed that the pluripotency factor OCT4/POU5F1 is consistently expressed across the entire bovine Day 7 blastocysts, similar to the observations by Simmet et al [55,56] and Kirchhof et al [57] in both in vivo and in vitro produced bovine embryos on days 7, 9, and 12. Furthermore, we observed an increased expression of POU5F1 and NANOG transcripts in blastocysts produced with miR-148b supplemented throughout the entire period of IVC or during days 1 to 4 of IVC to simulate the miRNA effect in the oviduct.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have indicated that NANOG activation does not rely on the embryonic activation of OCT4 [53,58]. However, the absence or very low levels of the epiblast marker NANOG in OCT4 knockout (KO) blastocysts on day 7 suggests that the maintenance of epiblast cells during the early stages of the second lineage differentiation fails in the absence of OCT4, thereby confirming the requirement of OCT4/POU5F1 for NANOG expression in bovine blastocysts [55]. In another study by the same group, OCT4 KO blastocysts generated through somatic cell nuclear transfer and zygote injection demonstrated that both epiblast maintenance and hypoblast differentiation rely on OCT4.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous research found that knocking down POU5F1 in mouse embryos did not influence cleavage or blastocyst development rate but did reduce the expression of TE-specific genes in the ICM [ 38 , 39 , 40 ]. Simmet et al (2022) [ 41 ] showed that POU5F1 is not required for blastocyst expansion and survival. In contrast, disruption of the POU5F1 locus in bovine hampered blastocyst development and demonstrated embryonic arrest at the morula stage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OCT4 frequently interacts with the SRY-box-containing transcription factor SOX2 to control the expression of several target genes, such as important transcription factors like NANOG [ 43 ]. In a study, embryos with the POU5F1-KO mutation reached the blastocyst stage by day 8 but lost NANOG expression, while SOX2 and GATA6 were unaffected [ 41 ]. SOX2 expression was found to be downregulated when POU5F1 expression was regulated by RNA interference [ 44 ].…”
Section: Discussionmentioning
confidence: 99%